Zeitenwende für die Außenwirtschaftspolitik - Katrin Kamin; Michael Bayerlein; Jacqueline Dombrowski (Wirtschaftsdienst, 2023)
Sowohl der Aufstieg Chinas als auch der Angriff Russlands auf die Ukraine haben gezeigt, dass wirtschaftliche Offenheit auch Abhängigkeiten schaffen kann, die für geopolitische Ziele genutzt werden. Ein vermehrter Einsatz von Handelsbeschränkungen und Sanktionen kann beobachtet werden. Dabei stellt sich die Frage, warum Autokratien als Handelspartner schwierig sind und wie mit ihnen in Zukunft umgegangen werden soll. – – There is currently a geopoliticisation of foreign policy, which is primarily driven by dependencies on autocratic systems. Autocracies are constantly on the rise, especially when measured by the percentage distribution of the world population. Even though the EU still trades with significantly more democracies than autocracies, trade relations with autocracies are often characterised by strong dependencies, especially with regard to critical raw materials such as lithium or magnesium. This also applies to the market for medical products, where China in particular uses its position as the main supplier to expand its geopolitical influence. This, together with the fact that autocracies are generally more likely to impose trade restrictions than democracies, means that the EU needs a strategy for how to handle trade with autocratic regimes in the future.
Keywords: F50; F68; F13; 330